The effectiveness of art therapy to reduce academic stress among students during online learning - Fitria, Linda; Putri, Ananda Maha; Fadli, Rima Pratiwi; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2022)
Many changes have occurred as a result of the COVID-19 pandemic and also be seen in the sphere of education, as learning methods are being transitioned from offline to online learning. These changes cause academic stress among students. Academic stress results in a drop in student learning motivation, and failure to complete lecture assignments on time. The researcher used this phenomena to conduct a one-design group experimental investigation on five academically challenged teenagers. Art therapy was utilized as the intervention, with an academic stress scale tool used to measure its effectiveness. During COVID-19, data collection and intervention operations are carried out directly through the use of health protocols. The Student-t Test is used to analyze the data with the help of Jeffreys' Amazing Statistics Program software. According to the findings of the study, an art therapy intervention was beneficial in reducing student academic stress in online learning.